Planting An Entrepreneurial Soul Through Activities Cooking Class - Fuadul Mustofa; Lailatul Rohmah; Erni Munastiwi (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Instilling an entrepreneurial spirit in early childhood is an important step in forming independent and innovative attitudes, skills and thoughts. Various ways can be done, including encouraging creativity and innovation, for example cooking class activities. This study aims to explore the influence of "cooking class" activities on the cultivation of entrepreneurial spirit in students TK Diponegoro Watumas. "cooking class" is a practical activity where students participate in the cooking process, ingredient management, and sales of culinary products. This study uses a qualitative method with a case study approach, involving direct observation, interviews, and document analysis. Interviews head school and 5 parent. The results of the study show that "cooking class" activities can foster entrepreneurial attitudes such as creativity, teamwork, time management, and marketing skills. This activity also increases the confidence and independence of students.